Pengaruh Intensitas Aset Tetap, Konservatisme Akuntansi, Pertumbuhan Penjualan terhadap Penghindaran Pajak - Malo, Sempratriz; Sugeng, Andry (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Tax avoidance practices remain a persistent challenge for governments in optimizing tax revenue. In Indonesia, the real estate and property sectors have been under scrutiny due to their complex asset structures and aggressive financial strategies that may facilitate tax avoidance. This study aims to empirically examine the influence of fixed asset intensity, accounting conservatism, and sales growth on tax avoidance. A quantitative, causal-associative approach was employed using secondary data from the financial statements of 13 real estate and property companies listed on the Indonesia Stock Exchange during 2019–2023. A total of 65 firm-year observations were analysed using panel data regression with the Random Effect Model, selected through Chow, Hausman, and Lagrange Multiplier tests. The results show that simultaneously, fixed asset intensity, accounting conservatism, and sales growth significantly influence tax avoidance. However, partial testing reveals that only sales growth has a significant positive impact on tax avoidance, while fixed asset intensity and accounting conservatism do not have significant effects. These findings indicate that increasing corporate revenues may lead to more aggressive tax planning behaviours, whereas asset intensity and conservative financial reporting do not necessarily reduce tax avoidance. The study contributes to the literature on corporate tax behaviour and provides insights for regulators in designing more effective tax policies for capital-intensive industries.